South Asia post 9/11 : searching for stability. - Observer Research Foundation; Rosa-Luxemburg-Stiftung. (New Delhi : Rupa & Co. in association with Observer Research Foundation, New Delhi, Rosa Luxemburg Foundation, Berlin, 2003)
Papers presented at international conference held on February 20-21, 2003 at New Delhi.
Includes bibliographical references and index.
Keywords: Terrorism -- South Asia -- Congresses; Religious pluralism -- South Asia -- Congresses